Alveolar bone loss in osteoporosis: a loaded and cellular affair? - Jonasson G; Rythén M (Dove Medical Press, 2016)
Grethe Jonasson,1,2 Marianne Rythén,2,3 1Department of Behavioral and Community Dentistry, Institute of Odontology, Sahlgrenska Academy, University of Gothenburg, Gothenburg, 2Research and Development Centre, Borås, 3Specialist Clinic for Pediatric Dentistry, Public Dental Service, Mölndal, Sweden Abstract: Maxillary and mandibular bone mirror skeletal bone conditions. Bone remodeling happens at endosteal surfaces where the osteoclasts and osteoblasts are situated. More surfaces means more cells and remodeling. The bone turnover rate in the mandibular alveolar process is probably the fastest in the body; thus, the first signs of osteoporosis may be revealed here. Hormones, osteoporosis, and aging influence the alveolar process and the skeletal bones similarly, but differences in loading between loaded, half-loaded, and unloaded bones are important to consider. Bone mass is redistributed from one location to another where strength is needed. A sparse trabeculation in the mandibular premolar region (large intertrabecular spaces and thin trabeculae) is a reliable sign of osteopenia and a high skeletal fracture risk. Having dense trabeculation (small intertrabecular spaces and well-mineralized trabeculae) is generally advantageous to the individual because of the low fracture risk, but may imply some problems for the clinician. Keywords: bone density, bone fracture, human, mandible, radiography, periodontitis